Analysis of Socio-Economic Benefits in ASA Bergending Community Development Program Through the Implementation of the Bio Circular Green Economic Model - DEWI LUQMANIA; Anjumiz Sunani; Febi Agus Dwi Riyanto (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
ASA BERGENDING program is a gender and environment-based community development initiative targeting survivors of Domestic Violence (DV) in Gending Village, Gresik Regency, East Java Province. With a holistic approach through the Bio Circular Green (BCG) economic model, this program does not only aim for psychosocial recovery but also economic empowerment and community-based environmental management. This article aims to analyze the social and economic benefits of implementing the BCG model in the program and how the BCG approach can strengthen community sustainability. The method used is a descriptive qualitative study based on secondary data. The results of the study show that ASA BERGENDING program is able to increase socio-economic benefits in the form of increasing individual capacity and psychosocial recovery, environmental-based economic empowerment, social transformation of community, institutional strengthening and replication, and measurable socio-economic impacts through an inclusive and participatory approach.